De novo Assembly and Characterization of Cajanus scarabaeoides (L.) Thouars Transcriptome by Paired-End Sequencing - Nigam, Deepti; Saxena, Swati; Ramakrishna, G.; Singh, Archana; Singh, N. K.; Gaikwad, Kishor (Frontiers in Molecular Biosciences, 2017)
Pigeonpea [Cajanus cajan (L.) Millsp.] is a heat and drought resilient legume crop grown mostly in Asia and Africa. Pigeonpea is affected by various biotic (diseases and insect pests) and abiotic stresses (salinity and water logging) which limit the yield potential of this crop. However, resistance to all these constraints is not readily available in the cultivated genotypes and some of the wild relatives have been found to withstand these resistances. Thus, the utilization of crop wild relatives (CWR) in pigeonpea breeding has been effective in conferring resistance, quality and breeding efficiency traits to this crop. Bud and leaf tissue of Cajanus scarabaeoides, a wild relative of pigeon pea were used for transcriptome profiling. Approximately 30 million clean reads filtered from raw reads by removal of adaptors, ambiguous reads and low-quality reads (3.02 gigabase pairs) were generated by Illumina paired-end RNA-seq technology. All of these clean reads were pooled and assembled de novo into 1,17,007 transcripts using the Trinity. Finally, a total of 98,664 unigenes were derived with mean length of 396 bp and N50 values of 1393. The assembly produced significant mapping results (73.68%) in BLASTN searches of the Glycine max CDS sequence database (Ensembl). Further, uniprot database of Viridiplantae was used for unigene annotation; 81,799 of 98,664 (82.90%) unigenes were finally annotated with gene descriptions or conserved protein domains. Further, a total of 23,475 SSRs were identified in 27,321 unigenes. This data will provide useful information for mining of functionally important genes and SSR markers for pigeonpea improvement.